(untitled) (Journal of Hama University, 2022)
Direct pulp capping is a conservative therapy frequently performed for preserving pulp vitality when the pulp is exposed caused by caries/cavity preparation/trauma.. Pulp damage may be caused by microorganisms, which survived in the dentin after the cavity preparation. To prevent this damage, direct pulp-capping materials placed directly over the pulp and localized under the permanent restoration must have good antimicrobial activity. The purpose of this study was to evaluation of the antibacterial efficacy of dental caries for Thyme with zinc oxide paste as a direct pulp capping material in comparison with calcium hydroxide by agar diffusion test. Caries blocks were taken from permanent teeth with impermeable deep occlusal caries with vital dental pulp. Samples were placed in BHI broth and incubated for 24 hours at 37 °C. 100 μL of the liquid culture, after adjusting its turbidity by a spectrophotometer at a wavelength of 600 nm, was inoculated into the blood agar medium after making two holes 5 mm diameter and 4 mm depth. One of the holes was filled with a mixture of Thyme oil and zinc oxide, and in the other with calcium hydroxide. After incubation at 37°C for 24 h, the results were read by measuring the diameter of the inhibition zone in millimeter. The data obtained is statistically analyzed using the independent samples T- Test (P≤ 0.05). Antibacterial efficacy of Thyme paste was lesser than calcium hydroxide paste ( P-value = 0.00 ). Thyme paste can’t be used as a direct pulp capping material due to its weak effectiveness against the bacteria of dental caries.